Validação das formas curtas da versão brasileira do Child Perceptions Questionnaire 11-14 (CPQ11-14) - Cintia Silva Torres (2008)
The need to evaluate the impact of oral health has led to the development of instruments to measure oral-health-related quality of life. One such instrument is the Child Perceptions Questionnaire (CPQ11-14), developed specifically for 11-to-14-year-old children. As this questionnaire was considered long (37 items), shorter forms were developed with 8 (Impact Short Form: 8 -ISF:8) and 16 items (Short Form Impact: 16 ISF:16) to facilitate use in the clinical setting and population-based health surveys. The aim of the present study was to translate and cross-culturally adapt these short forms of the CPQ11-14 for Brazilian Portuguese and test the reliability and validity of these versions for use on Brazilian children. The instruments were tested on a sample of 136 children, divided into three groups according to the diagnosis of dental caries and malocclusion: Group 1 children without untreated dental caries and without malocclusion; Group 2 children with untreated tooth decay and without malocclusion; and Group 3 children without untreated dental caries and with malocclusion. The properties of internal consistency, test-retest reliability, construct validity, discriminant validity and criterion validity were evaluated in the two short forms. The mean total score was 6.8 (±4.2) for the ISF:8 and 11.9 (±7.6) for the ISF:16 (p<0.001). Associations were found between oral disorders and the domains of the CPQ11-14 -ISF:8 and ISF:16 (p<0.05). Internal reliability was confirmed by Cronbachs alpha coefficient (0.70 and 0.84). Test-retest analysis revealed excellent reproducibility (intraclass correlation coefficients of 0.98 and 0.97). There was a significant association between the mean total score and clinical groups (p<0.05). Construct validity was satisfactory, revealing a significant correlation between total score and global indicators on each instrument. Criterion validity was appropriate, demonstrating a correlation between the instruments themselves. The present study demonstrated satisfactory psychometric properties, confirming that short forms of Brazilian version the CPQ11-14 are valid and applicable to children in Brazil.